Online Content Marketing as an Innovative Mechanism for Customer Relationship Management: A Field Study on a Sample of Customers of Egyptian Cellular Telecommunications Companies - Abd El-Aal, Mohamed (The Arab Journal of Administration, 2023)
This study aimed to demonstrate the impact of content marketing in its various dimensions (Content Relevance - Content Reliability - Content Value - Content Emotion - Content Attractiveness) on management the relationship with customers of Egyptian cellular communications companies, and to achieve this purpose, this study was based on the descriptive analytical approach, Where the questionnaire tool was used to collect primary data, and the researcher also relied on using the sample method for all customers of the Egyptian cellular telecommunications companies, as (370) questionnaires were distributed, of which (335) were subjected to statistical analysis. The study found that the level of perception of Egyptian cellular companies’ customers was high for each dimension of content marketing towards management the relationship with the customer, and the results showed a positive relationship with statistical significance between each of the dimensions of content marketing and management the relationship with the customer. The study recommended that Egyptian cellular telecommunications companies should pay attention to marketing content because of its effective role and impact in management the relationship with customers. It also recommended that the content provide accurate information about the products and services provided by telecommunications companies, in order to increase users ’confidence in the content provided..